Early fortification of enteral feedings for infants <1250 grams birth weight receiving a human milk diet including human milk based fortifier - Huston, Robert (J Neonatal Perinatal Med, 2020)
BACKGROUND: An exclusive human milk diet (EHM) including fortification with a human milk-based fortifier has been shown to decrease the occurrence of necrotizing enterocolitis (NEC) but growth velocity may be less for infants receiving EHM compared to a bovine diet. OBJECTIVE: The objective of this study was to determine if growth is improved by earlier fortification of breast milk for preterm infants supported with a human milk based fortifier. STUDY DESIGN: A multi-center retrospective cohort study of the outcomes of infants of 500– 1250 g birth weight whose breast milk feedings were fortified at >60 mL/kg/day (late) versus <60 mL/kg/day (early) of enteral feeding volume. RESULTS: Median±IQR range for gestational age (27.6±3.4 vs 27.0±2.9 weeks, p = 0.03) and chronic lung disease (CLD: 42.6 vs 27.6%, p = 0.008) were higher, and weight gain (12.9±2.6 vs 13.3±2.6 g/kg/day, p = 0.03) was lower in the late (N = 102) vs the early (N = 292) group. Adjusted multiple linear regression analysis found that early fortification was associated with improved growth velocity for weight (p = 0.007) and head circumference (HC) (p = 0.021) and less negative changes in z-scores for weight (p = 0.022) and HC (p = 0.046) from birth to discharge. Adjusted multiple logistic regression found that early fortification was associated with decreased occurrence of CLD (p = 0.004). No other outcomes, including NEC, were associated with early versus late fortification. CONCLUSION: The study results suggested that early HM fortification appears to positively affect growth for infants whose human milk feedings are fortified with a human milk based fortifier without adverse effects. The incidence of CLD was also reduced in the early fortification group.